An outreach telephone program for advanced melanoma supportive care: Acceptability and feasibility. (October 2019) - Fox, Jennifer; Janda, Monika; Bennett, Fiona; Langbecker, Danette
Abstract: Purpose: People with advanced melanoma face an uncertain trajectory as new treatments now have the potential to provide longer-term survival for some. However, the disease course is variable and unpredictable, with many expressing a need for better supportive care. This study aimed to investigate the acceptability and feasibility of extending an existing melanoma-specific self-referral or 'passive' telephone consultation support service to an 'active' outreach call to offer a supportive care program tailored to the needs of the patient. Method: Participants were enrolled by their oncology nurse into a single group pre-post intervention study. Participants received an outreach telephone call focused on knowledge and skill development. Participants completed questionnaires at baseline and four weeks post-intervention. Post-intervention interviews with patients and involved staff were used to explore acceptability and feasibility of the outreach service call. Results: Of 18 participants approached, 15 enrolled and 14 received the intervention. Staff time required for intervention delivery provided evidence for feasibility. Participants perceived the intervention as acceptable, and beneficial. In interviews, having someone with melanoma-specific knowledge to talk with was a key benefit of the outreach call program. Many participants expressed that they would have wished to receive the outreach call at an earlier stage, for example at the time of recurrence of/progression to advanced melanoma. Conclusions: Extending an existing self-referral support service model to use a more 'active' outreach approach is acceptable and feasible. The next step in the evaluation process for this intervention is a randomised controlled trial to determine effectiveness and cost-effectiveness. Highlights: Immune and targeted therapies for advanced melanoma may provide longer term survival for some. The advanced melanoma disease course is unpredictable with a need for better supportive care. An 'active' outreach call to offer a tailored supportive care program is acceptable and feasible. An outreach call at an earlier stage of an advanced melanoma diagnosis is preferable.